From maternal breath to infant's cells: Impact of maternal respiratory infections on infants ‘immune responses - Dauby, Nicolas; Flamand, Véronique (Frontiers in Pediatrics, 2022)
In utero exposure to maternally-derived antigens following chronic infection is associated with modulation of infants ‘immune response, differential susceptibility to post-natal infections and immune response toward vaccines. The maternal environment, both internal (microbiota) and external (exposure to environmental microbes) also modulates infant’s immune response but also the clinical phenotype after birth. Vertical transmission of ubiquitous respiratory pathogens such as influenza and COVID-19 is uncommon. Evidence suggest that in utero exposure to maternal influenza and SARS-CoV-2 infections may have a significant impact on the developing immune system with activation of both innate and adaptive responses, possibly related to placental inflammation. Here in, we review how maternal respiratory infections, associated with airway, systemic and placental inflammation but also changes in maternal microbiota might impact infant’s immune responses after birth. The clinical impact of immune modifications observed following maternal respiratory infections remains unexplored. Given the high frequencies of respiratory infections during pregnancy (COVID-19, influenza but also RSV and HMPV), the impact on global child health could be important.